"REFLECTIVE PRACTITIONER" AS A MEANS OF EFL INSTRUCTORS' PROFESSIONAL GROWTH (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Modifications to the educational system, especially in the area of foreign language instruction, necessitate creativity, fresh teaching proficiency, and familiarity with cutting-edge pedagogical and instructional tools. This article discusses the idea of a reflective practitioner, including its history, relationship to the idea of action research, impact on education and other fields, and essential elements. In addition, it clarifies the notions reflection-in-action and reflection-on-action. Furthermore, it provides an example of how it functions in real life.